Implantación de contabilidad comercial en “Imporloja”, de la ciudad de Loja; periodo junio-agosto del 2014 - Iñiguez Pineda, Gina Elizabeth (2015)
This degree work entitled "IMPLEMENTATION OF BUSINESS ACCOUNTING" IMPORLOJA "CITY OF LOJA, PERIOD JUNE-AUGUST 2014", was developed as required by Regulation of Academic System of the National University of Loja, to comply to pre-qualify the title of engineer in Accounting and Auditing requirement. The development of this research work is mainly done in compliance with the objectives and are leaving an established accounting system starting with establishing the initial inventory based on the source documents to the interview with its owner and a previous observation business. Knowing that currently accounting is essential in the live daily from businesses large or small due to their importance when making decisions to optimize your investments and get as useful as possible and thus achieve stay in the market